Fear of negative evaluation modulates the processing of social evaluative feedback with different valence and contexts. (3rd October 2022) - Zhang, Yinling; Li, Yanju; Mai, Xiaoqin
Abstract: Fear of negative evaluation (FNE) is a susceptible and maintaining factor of social anxiety disorders. However, the question, how people process negative evaluation is influenced by individual differences in FNE, is poorly understood. To clarify the habitual processing characteristics of individuals with different levels of FNE, electroencephalography was recorded when two groups of participants with high FNE (hFNE) and low FNE (lFNE) performed a social evaluation perception task in which the feedback context/source (human vs. a computer) and valence (thumb-up/like vs. thumb-down/dislike) were manipulated. We found effects of feedback source and valence on N1, P2, and P3, which reflect early attention, integrated perception, and elaborative processing, respectively, as well as general reward effects on reward positivity (RewP) across contexts. Importantly, compared to the lFNE group, the hFNE group showed larger midfrontal N1 and theta oscillation in response to negative feedback indicating dislike (vs. like), and also showed larger P3. These findings suggest that individuals with hFNE are more attentional vigilance to negative (vs. positive) social feedback, implying that individuals with different levels of FNE assign different implicit threat values to social-evaluation threat stimuli.